Implementasi Media Lumatika dan Dampaknya terhadap Minat Belajar Siswa SMP - Iwan; Haidar, Irajuana; Sari, Dian Ulfa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the implementation of LUMATIKA media on students' learning interest in mathematics learning at SMP Negeri 05 Poleang Timur. This study uses a mixed methods approach with an explanatory sequential design. The class selection uses Random Sampling and quantitative data are obtained through a learning interest questionnaire given before and after learning in the form of pretest and posttest, while qualitative data are obtained through observation, interviews, and documentation to strengthen the research results. The research subjects amounted to 3 students selected using purposive sampling technique. Quantitative data analysis was carried out through normality test and paired sample t-test to determine differences in students' learning interest before and after the use of LUMATIKA media. In addition, Cohen’s d calculation was used to determine the magnitude of the effect of using the media. The results of the normality test showed that the data were normally distributed with a calculated W value of 0.96 which is greater than the W table of 0.920 at a significance level of 5%. The results of the paired sample t-test showed a significance value of 0.001 (p < 0.05), which means that there is a significant difference between students' learning interest before and after the use of LUMATIKA media. The Cohen’s d value of 0.82 is in the large effect, as well as interviews conducted on students selected based on their level of learning interest, this shows that the implementation of LUMATIKA media has an effect on students' learning interest.